Pengaruh ?Islamic Branding, ?Religiusitas, Lifestyle ?terhadap Keputusan Pembelian Skincare ?di Kabupaten Gresik - Aliyah, Shufiyyatin; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2021)
For some people, skincare is included in the need. To meet these needs, there are cosmetic products that are specially formulated to treat skin health. It’s not just one or two brands that skincare products. This is what makes consumers have to be wise in choosing skincare products. Judging on the phenomenon, the author conducted a study with a view to knowing the effect of Islamic Branding, Religiosity, Lifestyle on skincare purchasing decisions in Gresik Regency. The approach used in this study is a quantitative approach and uses an explanatory research type. The rresults of this study are that Islamic Branding has no effect on purchasing decisions for skincare ing Gresik Regency. Meanwhile, Religiosity and Lifestyle affect the purchase of skincare in Gresik Regency.